Effects of steam explosion on phenolic compounds and dietary fiber of grape pomace. (1st January 2023) - Cui, Wenyu; Wang, Yunfu; Sun, Zhaoyue; Cui, Caifang; Li, Hang; Luo, Kaiyun; Cheng, Anwei
Abstract: Steam explosion (SE), as a high-efficient and environment-friendly pretreatment technology, was applied to pretreat the grape pomace. The results showed that SE increased the yield of free phenolics and flavonoids, but decreased the yield of bound phenolics and flavonoids. The content of total phenolics from grape pomace was much higher than that of total flavonoids. SE significantly decreased the contents of total monomeric anthocyanins and non-extractable proanthocyanins. (−)-Epicatechin and catechin were the most abundant ingredients in free extracts. After SE, most phenolic acids and flavonoids in the free extracts showed an increasing trend, while it is opposite in the bound extracts. SE increased the antioxidant activity of free extracts, but decreased the antioxidant activity of the bound extracts. SE can convert insoluble dietary fiber (IDF) into soluble dietary fiber (SDF) from grape pomace, and increase the oil-holding capacity (OHC) and sodium nitrite binding capacity (SNBC) of SDF. It can be concluded that an optimal SE condition at 1.2 MPa for 1 min could maximally increase the release of the phenolic compounds and enhance the antioxidant capacity; and the optimal SE condition for the extraction, OHC and SNBC of SDF in grape pomace was at 0.8 MPa for 3 min. Highlights: Steam explosion (SE) increased the yield of free phenolics and free flavonoids in grape pomace. (−)-Epicatechin and catechin were the abundance compounds in free extracts. SE enhanced the antioxidant activity of free extracts and decreased the activity of bound extracts. SE enhanced the yield of soluble dietary fiber and improved its physicochemical properties.